Atom-probe tomography : the local electrode atom probe - Miller, Michael K.; Forbes, Richard G. (Springer US, 2014)
This book aims to provide an introduction and overview of atom-probe tomography from a materials science perspective, a full introduction to underlying theory and to current understanding of the theory of laser-pulsed APT, and a careful account of how to prepare specimens, set up the appropriate conditions for tomography, analyse the experimental data, and present results. A special feature of this book is that it includes an updated historical account of the development of the underlying theory (including field evaporation), allowing readers to appreciate how theoretical understanding of the science behind the technique reached its present state.  This book is ideal for:  ·         beginners as well as more experienced researchers and scientists ·         those interested mainly in using the pulsed-laser local electrode atom probe for materials science ·         those interested in developing the technique and understanding the details of how it works